Staphylococcus saprophyticus From Clinical and Environmental Origins Have Distinct Biofilm Composition - Lawal, Opeyemi U.; Barata, Marta; Fraqueza, Maria J.; Worning, Peder; Bartels, Mette D.; Goncalves, Luisa; Paixão, Paulo; Goncalves, Elsa; Toscano, Cristina; Empel, Joanna; Urbaś, Malgorzata; Domiìnguez, Maria A.; et al. (Frontiers in Microbiology, 2021)
Biofilm formation has been shown to be critical to the success of uropathogens. Although Staphylococcus saprophyticus is a common cause of urinary tract-infections, its biofilm production capacity, composition, genetic basis and origin, are poorly understood. We investigated biofilm formation in a large and diverse collection of S. saprophyticus (n=422). Biofilm matrix composition was assessed in representative strains (n=63) belonging to two main S. saprophyticus lineages (G and S) recovered from human infection, colonization, and food-related environment using biofilm detachment approach. To identify factors that could be associated with biofilm formation and structure variation, we used a pan-GWAS approach. Almost all the isolates (91%; n = 384/422) produced biofilm. Among the 63 representative strains we identified eight biofilm matrix phenotypes, but the most common were composed of protein or protein-eDNA-polysaccharide-based (38%, 24/63 each). Biofilms containing protein-eDNA-polysaccharide were linked to lineage G and environmental isolates, whereas protein-based biofilms were produced by lineage S and infection isolates (p <0.05). Putative biofilm-associated genes namely aas, atl, ebpS, uafA, sasF, sasD, sdrH, splE, sdrE, sdrC, sraP, and ica genes were found with different frequencies (3-100%), but there was no correlation between their presence and biofilm production or matrix types. Notably, icaC_1 was ubiquitous in the collection while icaR was lineage G-associated, and only four strains carried a complete ica gene cluster (icaADBCR) except one that was without icaR. We provided evidence, using a comparative genomic approach that the complete icaADBCR cluster was acquired multiple times by S. saprophyticus and originated from other coagulase-negative staphylococci. Overall, the composition of S. saprophyticus biofilms were distinct in environmental and clinical isolates, suggesting that modulation of biofilm structure could be a key step in the pathogenicity of these bacteria. Moreover, biofilm production in S. saprophyticus is ica-independent and the complete ica gene cluster was acquired from other staphylococci.